Design Schematic Diagram of Endwall Control Panel to Electric Rail Train T3 Commuter Line - Faridahtul Syafiqoh; Usman Nursusanto; Rizqi Ervani (Universitas Islam Lamongan, 2025)
The number of Electric Rail Train (KRL) passengers in Indonesia increased by 20.62 million in February 2023, with an average of 736.5 thousand passengers per day, after the subsiding of Covid-19. In response to this increase and the push for more modern technology, PT KAI Commuter and PT INKA have collaborated to implement upgrades aimed at improving service quality and enhancing the efficiency of the train operation system. One of these upgrades was applied to the Commuter Line Electric Trains (KRL KCI) series 05 and 6000. The updates include the propulsion system, additional trainsets, and changes to the electrical panel layout. The reconfiguration of the electrical panel involved relocating the control system, previously located mainly under the train (underframe), now to both the underframe and the endwall. The endwall control panels are divided into two types: Endwall Control Panel A and Endwall Control Panel B.